2021
DOI: 10.2112/jcoastres-d-20-00135.1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Controls on the Particle Size of Resuspended Sediment from Sandy and Muddy Substrates in British Columbia, Canada

Abstract: A benthic annular flume, Sea Carousel, was deployed at both sand-dominated (Baynes Sound) and mud-dominated (Carrie Bay) stations in British Columbia, Canada, to examine the character of near-bed flow over these contrasting bottom types and its control on particle size of resuspended sediment. An assessment has also been made of the turbidityinduced drag reduction due to suspension of bottom sediments. The median sizes of suspended material from the sandy sites have been compared with the well-known Rouse theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
5
1
Order By: Relevance
“…Smoothed three-dimensional plots of G, C t , and d f showed a positive relationship of d f with G. That is, the larger the applied stress, the larger is the sedimentation diameter. This is opposite to that expected from Kassem, Sutherland, andAmos (2021), Lick, Huang, andJepsen (1993), Mehta (2014), andWinterwerp (2011), who suggest d f ; 1 ffiffiffi G p . A positive relationship is typical of silica sand (van Rijn, 1994) or dense aggregates suspended from an eroding bed.…”
Section: How Does Settling Flux Vary Between Differentcontrasting
confidence: 72%
See 2 more Smart Citations
“…Smoothed three-dimensional plots of G, C t , and d f showed a positive relationship of d f with G. That is, the larger the applied stress, the larger is the sedimentation diameter. This is opposite to that expected from Kassem, Sutherland, andAmos (2021), Lick, Huang, andJepsen (1993), Mehta (2014), andWinterwerp (2011), who suggest d f ; 1 ffiffiffi G p . A positive relationship is typical of silica sand (van Rijn, 1994) or dense aggregates suspended from an eroding bed.…”
Section: How Does Settling Flux Vary Between Differentcontrasting
confidence: 72%
“…Strong evidence suggests that, under conditions of flow, this diameter is controlled by shear rate (G) (Kassem, Sutherland, and Amos, 2021), whereas in still water, particle concentration and differential settling are important. An examination of factors influencing d f is thus justified and is the focus of the next section.…”
Section: How Does Settling Flux Vary Between Differentmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase in turbulent forces within the saltmarsh and mudflat tests at this low height may be attributed to irregularities and unevenness of their bed surfaces (Fig. 4) due to benthic activities and is an indication of the effect of bed roughness on turbulent flows 29,30. The calculated hydrodynamic roughnesses, z 0 = 10 -4 to 10 -6 m, were typical of muddy environments in the flatbed case 31 . A similar effect of bed roughness on the flow regimes can be observed from the mean velocities and bed shear stress (Table S2), with an increase in the downstream direction from P1 to P3.…”
Section: Discussionmentioning
confidence: 80%
“…Additionally, winter winds can enhance water exchange throughout the lagoon through mixing induced by wave and wind action. Such complex water motions often affect the size composition of the deposition particles (Kassem et al 2021). nMDS indicated that monthly means of flow velocity and diurnal flow velocity have both positive and negative correlations with the size fractions of deposited particles (Fig.…”
Section: Discussionmentioning
confidence: 99%